PM10 Retrieval From Spectroradiometer Measurements. - H, S Lim; Mat Jafri, M Z; Abdullah, K.; Saleh, N M; Al Sultan, Sultan (2005)
This study attempts to determine the aerosol optical thickness (AOT) from spectroradiometer data. The spectroradiometer is used to measure the atmospheric transmittances in a wide spectrum over Penang Island, Malaysia.